Pemberian Solid Decanter dan Pupuk P Terhadap Pertumbuhan dan Hasil Bawang Merah (Allium ascalonicum L.) di Tanah Ultisol - Mulya, Anugrah Hadi; Irianto, Irianto; Ermadani, Ermadani (Jurnal Media Pertanian, 2025)
Shallot (Allium ascalonicum L.) is an important horticultural commodity in Indonesia, but its productivity fluctuates, particularly in Jambi Province, where most agricultural land consists of low-fertility Ultisol soil. One solution to improve soil fertility is the use of solid decanter. This study aims to evaluate the effect of solid decanter on phosphorus availability from natural phosphate fertilizer, heavy metal reduction, and its impact on the growth and yield of shallots in Ultisol soil. Conducted in Kenali Asam, Jambi City, using a 4 × 4 factorial Randomized Block Design (RBD), the results show that the interaction between solid decanter and TSP fertilizer significantly affects plant height, bulb count, and bulb weight, but not leaf number or bulb size. The combination enhances nutrient absorption efficiency and supports optimal shallot growth. In conclusion, combining solid decanter and TSP fertilizer doses increases shallot yield, particularly in plant height, bulb count, and weight.